Future sustainability scenarios for universities: moving beyond the United Nations Decade of Education for Sustainable Development. (20th January 2016) - Beynaghi, Ali; Trencher, Gregory; Moztarzadeh, Fathollah; Mozafari, Masoud; Maknoon, Reza; Leal Filho, Walter
Abstract: As achievements of the completed United Nations Decade (2005–2014) of Education for Sustainable Development are contemplated globally, along with potential steps forward for the future, Member States have urged that this decade continue after 2014 through "The Future We Want"; the outcome document of the 2012 United Nations Conference on Sustainable Development. More recently, commitments to furthering the advancement of sustainable development through education have also been re-enforced in the recently adopted post-2015 Sustainable Development Goals. This study systematically analyzed the implications of sustainable development trends and future directions universities might take under a potential second decade (2015–2024). For this purpose, a model for generating "trend-based scenarios" is proposed, based upon a combination of various futures studies methods. Results suggest that the advancement of sustainability through societal collaboration and various functions such as education, research and outreach will increasingly constitute a core mission for universities. Projecting this trend out into the following decade, the authors frame possible future orientations through three unique scenarios; namely, a socially-, environmentally- and economically-oriented university. Pursuit of sustainable development through each of these would see unique and fundamental changes. These would affect the principle university mission, focus areas, emphasized disciplines, view of Education for Sustainable Development, core external partners, projects and outputs with external stakeholders, geographical focus, and main functions involved. The authors then examine how one or more of these scenarios might be actualized through various external and internal policy and incentive measures. The depiction of these three scenarios, along with potential measures to guide universities to either of these, provides scholars, university leaders and government policy makers with some conceptual and practical instruments to consider strategically how any of these futures might be realized.